2021
DOI: 10.1148/radiol.2021202423
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Trajectories of Regional Cerebral Blood Flow in Very Preterm Infants during Third Trimester Ex Utero Development Assessed with MRI

Abstract: N eurodevelopmental disabilities after premature exposure to extrauterine life remain prevalent and manifold and include motor, cognitive, behavioral, and socioaffective impairments (1). Notably, these neurodevelopmental impairments often take years to manifest, and early biomarkers of risk are needed to guide medical and rehabilitative interventions that mitigate risk.Coincident with premature extrauterine exposure are critical periods of brain development that may place the preterm infant at risk for impaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 35 publications
2
16
1
Order By: Relevance
“…6,19 By using multidelay ASL with longer postlabeling delays, we were able to overcome the slow CBF of neonates that would normally affect CBF estimations. In addition, we reconstructed the tCBF maps with multiple postlabeling delays, and during this process, we adjusted the T1 relaxation times for blood and tissue in neonates 6,7 because these values would differ between neonates and adults. T1 blood relaxation times were adjusted according to the hematocrit level of each neonate, and T1 tissue relaxation times for WM were adjusted according to the values obtained from synthetic MRI.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…6,19 By using multidelay ASL with longer postlabeling delays, we were able to overcome the slow CBF of neonates that would normally affect CBF estimations. In addition, we reconstructed the tCBF maps with multiple postlabeling delays, and during this process, we adjusted the T1 relaxation times for blood and tissue in neonates 6,7 because these values would differ between neonates and adults. T1 blood relaxation times were adjusted according to the hematocrit level of each neonate, and T1 tissue relaxation times for WM were adjusted according to the values obtained from synthetic MRI.…”
Section: Discussionmentioning
confidence: 99%
“…Although preterm neonates at termequivalent age would generally show less brain maturation compared with term neonates, 9,33 several studies have shown faster maturation in preterm neonates for specific brain regions. 7,9,33,34 Likewise, when a semiquantitative scoring system was applied, preterm neonates showed a higher degree of maturation in frontal and occipital WM compared with term neonates. 33 This advanced maturation in preterm neonates has been interpreted as a result of early exposure to the extrauterine environment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the influence mechanism of cortisol on the closure of the arterial catheter is unclear (17). Animal experiments have shown that cortisol can reduce prostaglandin synthesis by inhibiting phospholipase A, and can reduce the sensitivity of the arterial catheter to the prostaglandin expansion effect (18,19). Studies have also found that cortisol itself has a weak contractile effect on the artery (20).…”
Section: Discussionmentioning
confidence: 99%